Protective effect of nitric oxide on lettuce plants subjected to salt stress in semi-hydroponic system - da Silva Marques, Isabelly Cristina [UNESP]; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP]; Silva, Dayane Mércia Ribeiro [UNESP]; Bispo, Geane Lourenço [UNESP]; de Assis de Oliveira, Francisco (Springer Nature, 2024)
The use of low-quality water, with high salt concentrations, can cause several changes in plant metabolism, requiring strategies to facilitate its use in agriculture. Nitric oxide (NO) is an alternative among biological or synthetic substances that has promising effects on the physiological and biochemical responses of plants under salt stress conditions, as it promotes acclimation and favors plant growth. The aim of this research was to evaluate the effect of NO on lettuce plants grown under salt stress. A randomized block experimental design was used in a 5 × 2 factorial arrangement consisting of five concentrations of sodium nitroprusside (SNP) (0, 50, 100, 150, and 200 µM) and two salinity levels of the irrigation water (0.2 and 3.5 dS m−1: without and with salt stress, respectively). SNP concentrations were applied weekly (foliar application), totaling three applications during the crop cycle. The variables analyzed included: chlorophyll a fluorescence, lipid peroxidation, hydrogen peroxide, antioxidant enzymes, and proline content. The foliar application of NO by SNP donor, at concentrations between 100 and 150 µM provided greater efficiency of energy use in the photosystems and stimulated plant defense by increasing enzyme activity and proline contents, promoting cell detoxification. Therefore, exogenous application of NO, by donors, to plants under low-quality water conditions is important to mitigate the harmful effects of salt stress.
Keywords: Antioxidant enzymes; Chlorophyll a fluorescence; Salinity; Sodium nitroprusside; Vegetables